Cognition, Diagnosis, and Treatment of Alzheimer’s Disease: A Review - Qin, Yuping; Deng, Xiangxia; Zhang, Shuang (Recent Patents on Biotechnology, 2026)
As the global population ages, the health of older adults has become a growing concern. Alzheimer’s disease (AD) is a common ailment affecting older adults, but the diagnosis and treatment of AD are difficult given our insufficient understanding of the disease. This review article and patents aim to provide reliable information for patients and their families by presenting a detailed overview of the pathogenic factors, diagnostic methods, and clinical manifestation of AD, as well as advances in drug and physical therapies. The information presented here should help provide a more comprehensive understanding of AD for patients and their families and encourage family- or self-screening based on clinical manifestations, thus improving early AD detection. In addition, the current treatment methods for AD are summarized. Although a gold-standard treatment for AD is yet to be developed, controlled-release therapies and medications that slow disease progression or improve cognitive function are available. The appropriate treatment method depends on the patient’s diagnosis and the local medical level, and the effectiveness of the treatments may vary. Therefore, improving our understanding of AD and cognition-related symptoms in the public is necessary to improve early AD diagnoses. This review provides information that will facilitate self-screening for AD based on clinical manifestations, which can improve the early clinical diagnosis rate.
Keywords: recognition